Analisis Daya Dukung Lahan untuk Pengembangan Budi Daya Kerapu di Perairan Tambak Kecamatan Cilebar, Kabupaten Karawang - La Ode Alifatri; Sigid Hariyadi; Handoko Adi Susanto (Institut Pertanian Bogor, 2017)
The aims of this research were to analyze the land suitability and carrying capacity for groupers culture. The utilized methods were land suitability analysis and carrying capacity analysis. The results of land suitability analysis showed that the area which is fit very suitable criteria is 38.16 ha (17.13%), fit enough suitable is 118.27 ha (53.11%), and appropriate-conditional suitable is 66.26 ha (29.75%). The results of carrying capacity analysis resulted in an area of 156.43 ha which is very suitable for groupers culture development in KJT systems. This area could accommodate as much as 313 ponds which are equivalent to 626 units or 6.257 KJT boxes.